2018
DOI: 10.1002/bit.26595
|View full text |Cite
|
Sign up to set email alerts
|

Improved squalene production through increasing lipid contents in Saccharomyces cerevisiae

Abstract: Squalene, a valuable acyclic triterpene, can be used as a chemical commodity for pharmacology, flavor, and biofuel industries. Microbial production of squalene has been of great interest due to its limited availability, and increasing prices extracted from animal and plant tissues. Here we report genetic perturbations that synergistically improve squalene production in Saccharomyces cerevisiae. As reported previously, overexpression of a truncated HMG-CoA reductase 1 (tHMG1) led to the accumulation 20-fold hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 49 publications
(71 reference statements)
0
57
0
Order By: Relevance
“…(A) Squalene biosynthesis via MVA pathway in yeast, fungi, and algae. The engineering strategies for enhanced squalene production are as follows: overexpression of HMGR (Polakowski et al, 1998; Tokuhiro et al, 2009; Mantzouridou and Tsimidou, 2010; Dai et al, 2012, 2014; Zhuang and Chappell, 2015; Rasool et al, 2016a,b; Kwak et al, 2017; Paramasivan and Mutturi, 2017; Han et al, 2018; Huang et al, 2018; Wei et al, 2018) and SQS (Dai et al, 2014; Zhuang and Chappell, 2015; Rasool et al, 2016a,b), downregulation of SQE (Garaiová et al, 2014; Hull et al, 2014; Zhuang and Chappell, 2015; Rasool et al, 2016a,b; Han et al, 2018) in yeast; downregulation of SQE in algae (Kajikawa et al, 2015). (B) Squalene biosynthesis via MEP pathway in bacteria.…”
Section: Squalene Biosynthetic Pathway In Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…(A) Squalene biosynthesis via MVA pathway in yeast, fungi, and algae. The engineering strategies for enhanced squalene production are as follows: overexpression of HMGR (Polakowski et al, 1998; Tokuhiro et al, 2009; Mantzouridou and Tsimidou, 2010; Dai et al, 2012, 2014; Zhuang and Chappell, 2015; Rasool et al, 2016a,b; Kwak et al, 2017; Paramasivan and Mutturi, 2017; Han et al, 2018; Huang et al, 2018; Wei et al, 2018) and SQS (Dai et al, 2014; Zhuang and Chappell, 2015; Rasool et al, 2016a,b), downregulation of SQE (Garaiová et al, 2014; Hull et al, 2014; Zhuang and Chappell, 2015; Rasool et al, 2016a,b; Han et al, 2018) in yeast; downregulation of SQE in algae (Kajikawa et al, 2015). (B) Squalene biosynthesis via MEP pathway in bacteria.…”
Section: Squalene Biosynthetic Pathway In Microorganismsmentioning
confidence: 99%
“…Rapid and remarkable advances in genetic engineering, metabolic engineering and synthetic biology approaches over the last few decades have facilitated the insertion of heterologous genes and editing of the genome of an organism, enabling successful attempts to produce innumerable molecules of industrial importance (Martin et al, 2009; Stephanopoulos, 2012; Singh, 2014; Jullesson et al, 2015). Lately, a number of microorganisms have been engineered by inserting a squalene biosynthetic pathway or by the modification of existing biosynthetic pathway for over-production of squalene (Ghimire et al, 2009; Katabami et al, 2015;Han et al, 2018; Wei et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of the native diacylglycerol O-acyltransferase (DGA1) together in the squalene platform strain resulted in 320 ± 16.2 mg/L squalene, less than when only expressing SQS. Overexpression of the native DGA1 in combination with a truncated version of HMG in S. cerevisiae increased squalene titers, probably due to an increased lipid content providing storage for squalene accumulation (Wei et al, 2018). However, overexpression of DGA1 in Y. lipolytica did not benefit squalene production in the context of this study, likely due to the diversion of acetyl-CoA to lipid biogenesis (Figure 1).…”
Section: Triterpene Platform Strainmentioning
confidence: 65%
“…The excessive cytoplasmic accumulation of olefin oils such as squalene and terpene inflict toxic effects and metabolic stress on the yeast cell [43,44]. However, lipid droplets in yeast can only store small quantities of olefin oil due to the tight regulation of their biogenesis [45,46].…”
Section: Optimization Of Squalene Overproduction Via Overexpression Omentioning
confidence: 99%
“…DGA1 encodes diacylglycerol O-acyltransferase, catalyzes the critical step involved in the production of triacylglycerol (TAG) and stimulation of biogenesis of lipid droplets in yeast [49]. The previous study has shown that overexpression of DGA1 enhanced the accumulation of squalene via stimulating the biogenesis of lipid droplets in yeast [44].…”
Section: Optimization Of Squalene Overproduction Via Overexpression Omentioning
confidence: 99%